Together at Last: Trade Costs, Demand Structure, and Welfare - Mrázová, Monika; Neary, J. Peter (American Economic Review, 2014)
We show that relaxing the assumption of CES preferences in monopolistic competition has surprising implications when trade is restricted. Integrated and segmented markets behave differently, the latter typically exhibiting reciprocal dumping. Globalization and lower trade costs have different effects. The former reduces spending on all existing varieties, the latter switches spending from home to imported varieties; when demands are less convex than CES, globalization raises whereas lower trade costs reduce firm output. Finally, calibrating gains from trade is harder. Many more parameters are needed, while import demand elasticities typically overestimate the true elasticities, and so underestimate the gains from trade.